Universal scattering response across the type-II Weyl semimetal phase diagram - Ruessmann, P.; Weber, A. P.; Glott, F.; Xu, N.; Fanciulli, M.; Muff, S.; Magrez, A.; Bugnon, P.; Berger, H.; Bode, M.; Dil, J. H.; S. Blügel; et al. (PHYSICAL REVIEW B, 2018)
The discovery of Weyl semimetals represents a significant advance in topological band theory. They paradigmatically enlarged the classification of topological materials to gapless systems while simultaneously providing experimental evidence for the long-sought Weyl fermions. Beyond fundamental relevance, their high mobility, strong magnetoresistance, and the possible existence of even more exotic effects, such as the chiral anomaly, make Weyl semimetals a promising platform to develop radically new technology. Fully exploiting their potential requires going beyond the mere identification of materials and calls for a detailed characterization of their functional response, which is severely complicated by the coexistence of surface-and bulk-derived topologically protected quasiparticles, i.e., Fermi arcs and Weyl points, respectively. Here, we focus on the type-II Weyl semimetal class in which we find a stoichiometry-dependent phase transition from a trivial to a nontrivial regime. By exploring the two extreme cases of the phase diagram, we demonstrate the existence of a universal response of both surface and bulk states to perturbations. We show that quasiparticle interference patterns originate from scattering events among surface arcs. Analysis reveals that topologically nontrivial contributions are strongly suppressed by spin texture. We also show that scattering at localized impurities can generate defect-induced quasiparticles sitting close to the Weyl point energy. These give rise to strong peaks in the local density of states, which lift the Weyl node, significantly altering the pristine low-energy spectrum. Remarkably, by comparing the WTe2 and the MoTe2 cases we found that scattering response and topological transition are not directly linked. Visualizing the existence of a universal microscopic response to scattering has important consequences for understanding the unusual transport properties of this class of materials. Overall, our observations provide a unifying picture of the type-II Weyl phase diagram.